2016
DOI: 10.1089/ten.tec.2015.0349
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Responsive Bone Marrow Mesenchymal Stem Cell-Derived Smooth Muscle Cells Maintain Their Benefits to Augmenting Elastic Matrix Neoassembly

Abstract: Abdominal aortic aneurysms (AAA) represent abnormal aortal expansions that result from chronic proteolytic breakdown of elastin and collagen fibers by matrix metalloproteases. Poor elastogenesis by adult vascular smooth muscle cells (SMCs) limits regenerative repair of elastic fibers, critical for AAA growth arrest. Toward overcoming these limitations, we recently demonstrated significant elastogenesis by bone marrow mesenchymal stem cell-derived SMCs (BM-SMCs) and their proelastogenesis and antiproteolytic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…After 1 week in culture, porcine AV leaflets were harvested for protein isolation as described previously (17, 18). Briefly, the leaflets were flash frozen with liquid nitrogen and stored at −80°C overnight before being lyophilized for 24 h. The lyophilized tissues were harvested in T-PER lysis buffer (Thermo Fisher Scientific) containing 1% Halt™ protease inhibitor cocktail (Thermo Fisher Scientific) and homogenized using a Tissue Lyser II (Qiagen, Germantown, MD).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 1 week in culture, porcine AV leaflets were harvested for protein isolation as described previously (17, 18). Briefly, the leaflets were flash frozen with liquid nitrogen and stored at −80°C overnight before being lyophilized for 24 h. The lyophilized tissues were harvested in T-PER lysis buffer (Thermo Fisher Scientific) containing 1% Halt™ protease inhibitor cocktail (Thermo Fisher Scientific) and homogenized using a Tissue Lyser II (Qiagen, Germantown, MD).…”
Section: Methodsmentioning
confidence: 99%
“…The effect of hypoxia on the enzyme activity of MMPs 2 and 9 was analyzed using gel zymography (18, 20). A total of 10 and 4 μg of tissue and cell lysates, respectively, were loaded in each lane of 10% gelatin zymogram gels (Invitrogen) and run for 2 h at 125 V. Subsequently, the gels were washed with 2.5% v/v TritonX-100 for 30 min, incubated in substrate development buffer (G Biosciences, St. Louis, MO) for 48 h, stained with Coomassie Brilliant Blue (Bio-Rad), and de-stained with water until clear bands were visible.…”
Section: Methodsmentioning
confidence: 99%
“…74 The authors did not register any adverse impact of the SPIONs on the cells' viability, phenotype, elastic matrix synthesis, and elastogenesis-stimulatory and antiproteolytic properties and concluded that this can be a very useful approach for in situ AAA regenerative repair.…”
Section: Magnetic Tissue Engineeringmentioning
confidence: 98%
“…NPs can also be conjugated to the cell membrane of MSCs to ensure cell survival toward subsequent tumor inhibition ( Li et al, 2011 ). SMCs have aided in ECM regeneration and can be a worthwhile delivery vehicle to target the alveoli to regenerate the elastic matrix ( Swaminathan et al, 2016 ). Our lab has recently demonstrated significant elastogenesis by bone marrow MSC-derived SMC-like cells (BM-SMCs) and their pro-elastogenic and anti-proteolytic effects on rat aneurysmal SMCs.…”
Section: Extracellular Matrix Of the Lung Tissue Microenvironment In mentioning
confidence: 99%
“…Our lab has recently demonstrated significant elastogenesis by bone marrow MSC-derived SMC-like cells (BM-SMCs) and their pro-elastogenic and anti-proteolytic effects on rat aneurysmal SMCs. The BM-SMCs were loaded with super paramagnetic iron oxide nanoparticles (SPIONs) toward guiding them to the AAA wall using an applied external magnetic field ( Swaminathan et al, 2016 ). In vitro , the BM-SMCs stimulated elastin regeneration and attenuated proteolytic activity by cocultured aneurysmal SMCs both upon and without SPION labeling.…”
Section: Extracellular Matrix Of the Lung Tissue Microenvironment In mentioning
confidence: 99%